Impact of childhood trauma on cognitive function in patients with bipolar disorder - Zhang, Zhiyang; Zhou, Chenyu; Mao, Zhen; Sun, Yue; Zhao, Lei; Li, Tian; Wang, Chuanyue; Bo, Qijing (Frontiers in Psychiatry, 2025)
BackgroundPatients with bipolar disorder (BD) frequently exhibit cognitive impairments. However, the association between childhood trauma as a risk factor for BD and cognitive deficits remains ambiguous.ObjectiveTo investigate the relationship between childhood trauma and cognitive function among patients with BD.MethodsThe study included 90 patients with BD and 94 healthy controls (HC). Childhood trauma was assessed using the Childhood Trauma Questionnaire (CTQ), and cognitive function was evaluated using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The relationships between childhood trauma and cognitive function.ResultsIn BD group, childhood abuse and neglect were more prevalent than in HC group. Mood stabilizer use was positively associated with language abilities, while antipsychotic use negatively impacted attention. Emotional abuse predicted impaired immediate memory, with the number of episodes and valproate dosage negatively correlating with total RBANS scores, whereas education and mood stabilizer use showed positive correlations.ConclusionsThe incidence of childhood trauma was higher among BD than HC, and different types of childhood trauma had varying effects on different aspects of cognition. These studies will deepen the understanding of the complexity of BD and support the development of more effective treatment methods.